A simple low cost data acquisition system for remote sensing of relative humidity and temperature - Moghavvemi, M.; Faruque, M.O.; Eng, N.K.; Yip, S.C. (2001)
This paper presents a simple technique in combining analog circuit and digital circuit theory together with programming technique to control the hardware for remote sensing of temperature and relative humidity. The sensor circuit converts the relative humidity and temperature into an analog signal, which will then be applied, to a micro controller based data logger for storage purpose. The data is then transferred to the computer through RS232 standard serial port. The user interface program will be handling the data transfer between data logger and the computer as well as allowing the user to input some of the important parameters such as sampling interval and starting date and time for the logging operation. The system can perform in both real time and off line.